Corpora methods in studying regional language varieties, exemplified by geographically annotated Ukrainian and Russian corpora - Шведова, Марія Олексіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The paper briefly presents existing corpora resources featuring Ukrainian texts as well as the previous experience in corpora-based studies of national language varieties (eg British vs. American English, New world Englishes, varieties of Spanish, Russian language in Belarus). The author has built two large corpora, respectively of the (written standard-oriented) Russian language in Ukraine (the so-called Ukrainian Russian) and of the Ukrainian language. Both corpora feature metatextual annotation by the regions where the texts were created (including, for Ukrainian, different countries of diaspora). The paper describes the main properties of these corpora and features examples of corpora-based lexical studies: borrowings in Ukrainian Russian (as compared to the standard of Russia proper, represented in the Russian National Corpus) and geographically distributed synonyms in Ukrainian.